Impact of age, hypercholesterolemia, and the vitamin D receptor on brain endogenous β‐amyloid peptide accumulation in mice. (18th August 2021) - Peng, H. Benson; Bukuroshi, Paola; Durk, Matthew R.; Grootendorst, Paul; Yan, Xiaoyu; Pan, Sophie R.; de Lannoy, Ines A. M.; Pang, K. Sandy
Abstract: Age, hypercholesterolemia, and vitamin D deficiency are risk factors that increase the brain accumulation of pathogenic β‐amyloid peptides (40 and 42), precursors leading to Alzheimer's disease (AD) in humans. The relative changes accompanying aging, high cholesterol, and/or treatment of calcitriol, active vitamin D receptor (VDR) ligand, under normal physiology are unknown. We examined these relative changes in C57BL/6 mice of ages 2, 4–8, and more than 10 months old, which were fed a normal or high fat / high cholesterol diet and treated with calcitriol, active ligand of the vitamin D receptor (0 or 2.5 μg/kg ×4, intraperitoneally, every other day to elicit cholesterol lowering in liver). Aβ40 but not Aβ42 accumulation in brain and lower P‐glycoprotein (P‐gp) and neprilysin protein expressions for Aβ efflux and degradation, respectively, were found to be associated with aging. But there was no trend for BACE1 (β‐secretase 1, a cholesterol‐sensitive enzyme) toward Aβ synthesis with age. In response to calcitriol treatment, P‐gp was elevated, mitigating partially the age‐related changes. Although age‐dependent decreasing trends in mRNA expression levels existed for Cyp46a1, the brain cholesterol processing enzyme, whose inhibition increases BACE1 and ApoE to facilitate microglia Aβ degradation, mRNA changes for other cholesterol transporters: Acat1 and Abca1, and brain cholesterol levels remained unchanged. There was no observable change in the mRNA expression of amyloid precursor protein (APP) and the influx (RAGE) and efflux (LRP1) transporters with respect to age, diet, or calcitriol treatment. Overall, aging poses as a risk factor contributing to Aβ accumulation in brain, and VDR‐mediated P‐gp activation partially alleviates the outcome. Abstract : Age, hypercholesterolemia, and vitamin D deficiency are known risk factors that increase the brain accumulation of pathogenic β‐amyloid peptides of 40 and 42 amino acid lengths, precursors leading to Alzheimer's disease (AD) in humans. We tested this hypothesis in different age hypercholesterolemic C57BL/6 mice, which were fed a high fat / high cholesterol diet with or without calcitriol treatment, the active vitamin D receptor (VDR) ligand. Our findings reveal that age poses as a risk factor contributing to Aβ accumulation in brain and VDR‐mediated P‐gp activation partially alleviates the outcome.